Fuel demand, road transport pollution emissions and residents' health losses in the transitional China. (January 2016) - YANG, Sheng; HE, Ling-Yun
Highlights: China's provincial economies are assumed to be independent "economic entities". We study fuel demand and health losses in the context of fiscal decentralization. The concept of pollution emissions elasticities is proposed and quantified. In a simplified framework, health losses are estimated empirically in real scenarios. Abstract: In recent years, China's rapid economic growth resulted in serious air pollution, which caused substantial losses to economic development and residents' health. In particular, the road transport sector has been blamed to be one of the major emitters. During the past decades, fluctuation in the international oil prices has imposed significant impacts on the China's road transport sector. Therefore, inspired by Li and Zhou (2005), we propose an assumption that China's provincial economies are independent "economic entities". Based on this assumption, we investigate the China's road transport fuel (i.e., gasoline and diesel) demand system by using the panel data of all 31 Chinese provinces except Hong Kong, Macau and Taiwan. To connect the fuel demand system and the air pollution emissions, we propose the concept of pollution emissions elasticities to estimate the air pollution emissions from the road transport sector, and residents' health losses by a simplified approach consisting of air pollution concentrations and health loss assessment models under different scenarios based on real-world oil price fluctuations. Our framework, to the best of our knowledge, is the first attempt to address the transmission mechanism between the fuel demand system in road transport sector and residents' health losses in the transitional China.